Polarized macrophages show diverse pro-angiogenic characteristics under normo- and hyperglycemic Conditions - Shariatzadeh, Mahnaz; Payán-Gómez, César; Kzhyshkowska, Julia; Dik, Willem A.; Leenen, Pieter J. M. (International journal of molecular sciences, 2025)
Angiogenesis plays a crucial role in solid tumor growth. Ischemia and inflammation induce various angiogenic mediators, and patient metabolic conditions importantly influence this process. Macrophages closely interact with the vascular system and regulate angiogenesis through pro/anti-angiogenic factors. Traditionally, pro-angiogenic activity has been attributed to M2-like macrophages. We question this, as recent evidence suggests that also M1-like macrophages can be pro-angiogenic. Therefore, the aim is to identify the pro/anti-angiogenic gene expression profiles of human polarized macrophages unbiasedly. We also examine the effect of hyperglycemia on angiogenic gene expression, reflecting its role in diabetes and other metabolic conditions. Bioinformatic analysis was performed on the angiogenesis-related gene expression profiles of CD14+ monocyte-derived M1(IFN-γ)- and M2(IL-4)-polarized macrophages. The top differentially expressed genes were selected for validation. Macrophages were generated in vitro and polarized to M1(IFN-γ) and M2(IL-4/IL-6) cells under standard/hyperglycemic conditions. After immunophenotypic confirmation, selected gene expression was quantified using qPCR. IL-4 and IL-6 induce distinct M2-like phenotypes with mixed pro/anti-angiogenic gene expression. Remarkably, IFN-γ stimulation also increases several pro-angiogenic genes. Hyperglycemia affects the angiogenic expression profile in both M1- and M2-like macrophages, although distinctive identities remain intact. The pro-angiogenic phenotype is not limited to M2-polarized macrophages. Both M1- and M2-like macrophages express complex pro/anti-angiogenic gene profiles, which are only mildly influenced by hyperglycemia.
Gesehen am 26.08.2025